2013
DOI: 10.3390/medicina48120096
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Endovascular Treatment of Aortoiliac Occlusive Disease

Abstract: The rate of endovascular interventions for iliac occlusive lesions is continuously growing. The evolution of the technology supporting these therapeutic measures improves the results of these interventions. We performed a review of the literature to report and appreciate short-and long-term results of endovascular stenting of iliac artery occlusive lesions. The Medline database was searched to identify all the studies reporting iliac artery stenting for aortoiliac occlusive disease (Trans Atlantic Inter-Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…22,23 Further studies have shown that using covered iliac stents for TASC C and D lesions is associated with favorable technical success, hence this is becoming a common technique to address AIOD. [6][7][8]10,[21][22][23][24] When using kissing stents in severe AIOD, however, the positioning of the stents and the discrepancy between the stented lumen and the aortic lumen ("radial mismatch") can have a negative impact on patency. 7,10,22 The CERAB technique aims to minimize this radial mismatch and achieve a more "anatomical" distal aortic and iliac reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Further studies have shown that using covered iliac stents for TASC C and D lesions is associated with favorable technical success, hence this is becoming a common technique to address AIOD. [6][7][8]10,[21][22][23][24] When using kissing stents in severe AIOD, however, the positioning of the stents and the discrepancy between the stented lumen and the aortic lumen ("radial mismatch") can have a negative impact on patency. 7,10,22 The CERAB technique aims to minimize this radial mismatch and achieve a more "anatomical" distal aortic and iliac reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]10,[21][22][23][24] When using kissing stents in severe AIOD, however, the positioning of the stents and the discrepancy between the stented lumen and the aortic lumen ("radial mismatch") can have a negative impact on patency. 7,10,22 The CERAB technique aims to minimize this radial mismatch and achieve a more "anatomical" distal aortic and iliac reconstruction. 6,7,11 The CERAB procedure also moves the aortic bifurcation proximally, which mimics the mechanics of a bifurcated graft used in open aortoiliac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the intraprocedural complications of IAS can be managed conservatively. Early mortality following iliac stent implantation has been reported in several studies and ranged from 0.7% to 3.6% [ 2 , 4 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomographic angiography has pretermitted digital subtraction angiography in imaging (2) and endovascular therapy has become the treatment of choice for debilitating aortoiliac occlusive disease in patients complaining of lower limb claudication (3). This growing interest for percutaneous transluminal angioplasty is based on its safety, technical feasibility (4), and non-invasive nature compared with open surgery along with lower mortality and infection rates (5).…”
Section: Introductionmentioning
confidence: 99%